Museums in the German art world from the end of the old regime to the rise of modernism - Sheehan, James J. (Oxford University Press, 2000)
Combining the history of ideas, institutions and architecture, this study shows how the museum both reflected and shaped the place of art in German culture from the late-18th to the early-20th century. On a broader level, it explains the origin and character of the museum's role in modern culture.